Modeling path capacity in multi-hop IEEE 802.11 networks for QoS services - Wang, Kun; Yang, Fan; Zhang, Qian; Xu, Yinlong (IEEE Transactions on Wireless Communications, 2007)
QoS provisioning in multi-hop IEEE 802.11 networks is very challenging due to the interference nature of wireless medium and the contention-based behavior among neighboring nodes. In such networks, one of the key questions for QoS support is: given a specific topology and traffic condition, how much bandwidth can be utilized along a path in the network without violating QoS demand of existing traffic? Considering that in general QoS-sensitive traffic has the well-controlled sending rate, one key observation is that the network unsaturated condition should be considered. Another observation is that, not only the interaction between the new traffic and the existing ones that can be sensed (by the new one), but also the interaction between the new traffic and the traffic that is hidden but can have influence upon the new one should be studied. Based upon the above observations, we propose an analytical model for multi-hop IEEE 802.11 networks to calculate how much bandwidth can be utilized along a path without violating the QoS requirements of existing traffic. A notion, "free channel time", which is the time allowed for a wireless link to transmit data, is introduced to analyze the path capacity. Simulation results demonstrate that our proposed analytical model can accurately predict the path capacity under various network conditions without breaking QoS demands of all existing traffic